Transformational leadership and job performance in the collaborators of a institute of education private higher of Arequipa, Peru, 2024 - Fernandez Sanchez, Diego Gonzalo (2024)
Objective: Identify the relationship between transformational leadership and job performance in the collaborators of a institute of education private higher in the city of Arequipa, Peru, 2024. Materials and methods: The study was of a basic type, of non-experimental design and a cross-sectional section; besides, it also had correlational scope and was developed under a quantitative approach. The population consisted of a total of 58 collaborators and as data collection instruments is worked with two questionnaires, one for each variable; both instruments were validated by expert judgment. Results: Deficiencies were evidences regarding the transformational leadership variable. Likewise, there is no good integration of the staff, since the institution does not take into account professional development, since it does not provide much trainings. All of this is reflected in the performance of the collaborators, who are at a medium level of satisfaction. Conclusions: There is a direct and significant relationship between transformational leadership and job performance (r = 0.712).